EFEK TONIK EKSTRAK DAUN KENIKIR (Cosmos caudatus Kunth.) TERHADAP MENCIT (Mus musculus) GALUR SUB SWISS WEBSTER SERTA SUMBANGANNYA PADA PEMBELAJARAN BIOLOGI SMA - Eka Mailisdiani; Riyanto Riyanto (Jurnal Pembelajaran Biologi: Kajian Biologi dan Pembelajarannya, 2016)
Abstract: Research of kenikir leaves ethanol extract were conducted to determine its tonic effect on mice. The method of study is the experimen method which is addressed with a completely randomized design. Sample using 24 male mice, consisted of four treatments and six replications. Treatment dosage were 0 mg/10 g BW, 7 mg/10 g BW, 14 mg/10 g BW and 28 mg/10 g BW. Swim test method was to determine of tonic effect on mice. Swimming duration of mice were analyzed with analysis of variance and test of calculations Least Significant Different (LSD). The results showed an average swimming duration of mice were highest at dose of 28 mg/10 g BW is 814,33 sec. Analysis of variance showed that kenikir leaves ethanol extract effected in increasing highest swimming duration at dose 28 mg/10 g BW. It can be concluded that kenikir leaves ethanol extract were potentialy as a tonic. The results of this study can be contributed to additional mater information of Biological lesson at eleven grade of Senior High School at first term on basic competation 3.5 about the tissue structure ofÂ  movement organ system and connect with its bioprocess. Keywords : kenikir leaves, swimming duration, tonic effect, mice.